La Ehrlichiosis canina: Ehrlichia canis (caso clínico) (2017)
Ehrlichiosis is a worldwide disease, it is endemic in tropical and subtropical countries where seroprevalence may be up to 33%. Ehrlichia spp. corresponds to a group of intracellular gram negative bacteria, of the family Rickettsiae, which are considered potentially zoonotic. These need a mammal as a reservoir, and an arthropod as a vector for transmission; its main vectors are arthropods belonging to the genus Ixodes spp. and Rhipicephalus spp. Ehrlichiosis is a multisystem infectious disease that due to proliferation of their vectors each day becomes more common in veterinary casuistry. Patients with this condition may be treated pharmacologically and clinically exit successfully, however the owner usually comes with patient in an advanced stage of the disease, a situation in which the multisystem failure is impossible to control, so death occurs.